2008
DOI: 10.1073/pnas.0810376105
|View full text |Cite
|
Sign up to set email alerts
|

DNA energy landscapes via calorimetric detection of microstate ensembles of metastable macrostates and triplet repeat diseases

Abstract: Biopolymers exhibit rough energy landscapes, thereby allowing biological processes to access a broad range of kinetic and thermodynamic states. In contrast to proteins, the energy landscapes of nucleic acids have been the subject of relatively few experimental investigations. In this study, we use calorimetric and spectroscopic observables to detect, resolve, and selectively enrich energetically discrete ensembles of microstates within metastable DNA structures. Our results are consistent with metastable, ''na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 84 publications
5
39
0
Order By: Relevance
“…There is no significant gain in the thermodynamic driving forces for larger repeat bulge loops relative to the duplex state compared to smaller bulge loops. There may, however, be a more pronounced activation energy barrier/ kinetic trap that makes larger repeat bulge loops persist more easily than smaller repeat bulge loops . There may also be potential higher order interactions within larger bulge loops; such as, branching or loops folded back on themselves.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no significant gain in the thermodynamic driving forces for larger repeat bulge loops relative to the duplex state compared to smaller bulge loops. There may, however, be a more pronounced activation energy barrier/ kinetic trap that makes larger repeat bulge loops persist more easily than smaller repeat bulge loops . There may also be potential higher order interactions within larger bulge loops; such as, branching or loops folded back on themselves.…”
Section: Resultsmentioning
confidence: 99%
“…Using oligonucleotide based models, we and others have shown that repeat sequences can form bulge loop ensembles of closely related structures stabilized by intramolecular interactions between the loop bases. Reversion of these structures to the more stable duplex state is inhibited at ambient temperature but occurs at elevated temperature . In other words, these bulge loops form metastable complexes that require input of external energy in order to revert to the more thermodynamically stable Watson‐Crick duplex state.…”
Section: Introductionmentioning
confidence: 99%
“…23 Others have reported various structural forms of trinucleotide repeats and suggested the impact that such variations might have upon instability. 24 The slower migration of these extra species suggested that multiple structural conformations may be formed by each oligo; when denatured with formamide prior to native electrophoresis or when run on denaturing gels, each oligo ran as a single species (Figure S3 of the Supporting Information). Notably, gel purification of each of the J4/5 species resulted in a mixture of the two species, suggesting that they may be interconverting.…”
Section: Resultsmentioning
confidence: 99%
“…To assess potential energetic origins of such coupled biological events, we have evaluated the impact of such proximal pairs of lesions/repair intermediates on the thermodynamic properties of triplet repeat DNAs. To this end, we have site specifically incorporated 8oxodG (O) and/or tetrahydrofuran (F), a stable abasic site analog, in place of guanidine residues located in opposite strands within oligonucleotide models of slipped DNA structures we previously have described 20, 49, 50. Our choice of 8oxodG is dictated by the observation that deletion of OGG1, the main glycosylase involved in 8oxodG lesion repair, significantly reduces the likelihood of DNA expansion in mouse models of Huntington's disease 17.…”
Section: Introductionmentioning
confidence: 99%